Some Strategies to Teach General English Vocabulary to Intermediate Students. A Case Study at Binh Thuan College - Nguyen Thi Dung (RIRAI Publisher, 2023)
This study aims to consider the distribution of multiple intelligences among students in order to apply some strategies to teach general English vocabulary to intermediate students of Binh Thuan College (BTC), Vietnam in academic year 2022-2023. The research participants were 35 students of BTC. Based on the data collected, there were 3 strong intelligences including Bodily-Kinesthetic Intelligence, Musical Intelligence, and Visual-Spatial Intelligence. Consequently, to teach vocabulary topics in 8 units of student’s books like jobs, sports, free-time activities, places in a city, common adjectives, things in a house, food and drink, appearance, clothes and colors, vacation activities, vacation items, daily activities, personality adjectives, hobbies and interests, the researcher used realia as well as mime, action, and gesture with support of the games and songs as strategies to teach vocabulary through classroom activities concerned about music, physical movement, and visuals.